Individual and community-level risk factors of women's acceptance of intimate partner violence in Ethiopia: multilevel analysis of 2011 Ethiopian Demographic Health Survey - Emiru Merdassa Atomssa; Araya Abrha Medhanyie; Girmatsion Fisseha (BMC, 2021)
Abstract Background The prevalence of Intimate partner violence (IPV) is higher in societies with higher acceptance of norms that support IPV. In Ethiopia, the proportion of women's acceptance of IPV was 69%, posing a central challenge in preventing IPV. The main objective of this study was to assess the individual and community-level factors associated with women's acceptance of IPV. Methods Two-level mixed-effects logistic regression was applied to the 2011 Ethiopia Demographic and Health Survey data. A total of 16,366 women nested in the 596 clusters were included in the analysis. Results The acceptability of the IPV was estimated to be 69%. Among the individual-level factors: women's education with secondary and above (AOR = 0.38; 95% CI 0.29-0.52), partner's education secondary and above (AOR = 0.71; 95% CI 0.54-0.82), women aged 35-49 years (AOR = 0.67; 95% CI 0.54-0.82), fully empowered in household level decision making (AOR = 0.67; 95% CI0.54-0.81), literate (AOR = 0.76; 95% CI 0.62-0.92), and perceived existence of law that prevents IPV (AOR = 0.56; 95% CI 0.50-0.63) were significantly associated with women's acceptance of IPV. Similarly, rural residence (AOR = 1.93; 95% CI 1.53-2.43) and living in the State region (AOR = 2.37; 95% CI 1.81-3.10) were significantly associated with the women's acceptance of IPV among the community-level factors. Conclusion Both individual and community-level factors were significant risk factors for the acceptability of intimate partner violence. Women's education, women's age, women's empowerment, partner education level, perceived existence of the law, and literacy were among individual factors. State region and residence were among community-level risk factors significantly associated women's acceptance of IPV.